2015
DOI: 10.3177/jnsv.61.8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Formylcobalamin and Propionylcobalamin, Novel Acylcobalamins

Abstract: Summary Formylcobalamin (formyl-Cbl), a C1-unit carrying corrinoid, and propionylcobalamin (propionyl-Cbl) were synthesized for the fi rst time, and their properties were compared with those of acetylcobalamin (acetyl-Cbl). Formyl-Cbl, acetyl-Cbl, and propionyl-Cbl were decomposed by a NH2OH treatment, forming formo-, aceto-, and propionohydroxamic acids, respectively, which offers a proof for the presence of "activated" acyl groups and for their structures of Co-acyl-Cbls. These results, together with chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…We have actually synthesized formylcobalamin and confirmed that it is unstable and gradually decomposes to OH-Cbl. 57 The holoenzymes of DD and GD are readily inactivated by O 2 in the absence of substrate. 7,16,18 Schwartz and Frey reported that holoDD reacts with O 2 to form peroxyadenosylcobalamin that is then decomposed to OH-Cbl and peroxyadenosine.…”
Section: ■ Discussionmentioning
confidence: 99%
“…We have actually synthesized formylcobalamin and confirmed that it is unstable and gradually decomposes to OH-Cbl. 57 The holoenzymes of DD and GD are readily inactivated by O 2 in the absence of substrate. 7,16,18 Schwartz and Frey reported that holoDD reacts with O 2 to form peroxyadenosylcobalamin that is then decomposed to OH-Cbl and peroxyadenosine.…”
Section: ■ Discussionmentioning
confidence: 99%